Pengembangan Kemampuan Babinsa Dalam Monitoring Dan Evaluasi Pembangunan Desa Berbasis Teknologi Internet OF THINGS (I0T) - panggabean, sarma; Ernawati Br. Surbakti; Hennilawati (LPPM Universitas HKBP Nommensen, 2025)
Village Guidance Non-Commissioned Officers (Babinsa) serve as the spearhead of the Indonesian Army (TNI AD) in fostering good relations between the TNI and the local community. The Babinsa's primary duty is to help maintain security and order within the community, as well as to develop village potential through development programs organized by the government and the TNI. Based on this duty, the Babinsa's rapid response in completing its main task is to conduct early detection by responding quickly and responsively to any problems that arise. This requires the Babinsa to be able to utilize internet-based science and technology for various purposes in the village, such as increasing communication and information efficiency, and supporting village development. For example, the use of instant messaging applications for coordination with residents, village websites for information transparency, and digital applications for village administration management. In addition, Babinsa can also use the internet to provide education and training to the community, as well as monitor potential threats in their assigned areas. The use of internet-based technology (IoT) namely Instant Messaging Applications (WhatsApp), Village Websites (SISKEUDES, Panic Button Applications), Social Media, CCTV can be used by Babinsa to support their monitoring and evaluation duties in their assigned villages.